Blood Metabolic Profile of Transhumant Baruwal Sheep Grazing Pastures of Two Different Altitudes at Similar Temperature Humidity Index - Barsila, Shanker Raj; Neupane, Grishma; Chhetri, Rupak Khatri (Journal of Agriculture and Resource Management, 2024)
The current study was conducted on native Baruwal sheep reared often in transhumance systems in Nepal. The main objective of the study was to examine how altitude affects some physiological and serum chemistry variables, as well as the haematology of these animals. 24 adult animals, 18 nonpregnant and nonlactating females and 6 intact males were discovered in a transhumance flock. Climate data was acquired and physiological measures (rectal temperature (RT), respiration rate (RR), and pulse rate (PR)) were evaluated when the sheep were in two stopovers at altitudes of 2,393 m asl in March and 3,391 m asl in June. We collected and examined grazing sward samples for close examination and blood samples for specific haematological and serum chemical traits. Both stopovers' settings fell within the sheep's thermo-comfort zone, and their pastures had the maximum crude protein content. According to statistical analysis, there was a significant (p